Literature Review: Complications and Management of Post Tonsillectomy Patients with Chronic Tonsillitis - Suryani, Elsa Indah; Asriantin, Isna; Pramesti, Evane Dyahayu; Hairy, Fathinah Salsabilla (Jurnal Biologi Tropis, 2025)
Chronic tonsillitis is a chronic inflammation of the palatine tonsils caused by a viral or bacterial infection, particularly Group A beta-hemolytic Streptococcus pyogenes. Tonsillitis commonly affects children aged 5-12 years and is a major health problem in the ENT-KL field in Indonesia. The prevalence is around 3.8%. Chronic tonsillitis can cause tonsil enlargement, which can interfere with the respiratory tract and lead to complications. This article is based on a literature review, compiling referen ces from several sources, including PubMed, Google Scholar, ScienceDirect, and ResearchGate. The process involved reading the titles, abstracts, and content of the articles to validate the sources used. Chronic tonsillitis is caused by a viral or bacterial infection that causes repeated inflammation of the tonsils, due to poor oral hygiene, allergies, and inadequate treatment. Clinical manifestations include a sore throat, enlarged tonsils, and respiratory distress. Tonsillitis is diagnosed through a history, physical examination, and supporting tests. Management consists of medication with antibiotics and oral hygiene, as well as surgical tonsillectomy if obstruction or recurrent infection occurs. Post-tonsillectomy complications include bleeding and infection, which must be treated promptly. Both medical and surgical therapy are effective in treating tonsillitis. During tonsillectomy, several factors must be monitored, including post-operative bleeding and infection. Prevention includes maintaining good hygiene and a healthy lifestyle.